Papillon-Lefèvre syndrome patient reveals species-dependent requirements for neutrophil defenses - Ole E. Sørensen; Stine N. Clemmensen; Sara L. Dahl; Ole Østergaard; Niels H. Heegaard; Andreas Glenthøj; Finn Cilius Nielsen; Niels Borregaard (The Journal of Clinical Investigation, 2014)
Papillon-Lefèvre syndrome (PLS) results from mutations that inactivate cysteine protease cathepsin C (CTSC), which processes a variety of serine proteases considered essential for antimicrobial defense. Despite serine protease–deficient immune cell populations, PLS patients do not exhibit marked immunodeficiency. Here, we characterized a 24-year-old woman who had suffered from severe juvenile periodontal disease, but was otherwise healthy, and identified a homozygous missense mutation in CTSC indicative of PLS. Proteome analysis of patient neutrophil granules revealed that several proteins that normally localize to azurophil granules, including the major serine proteases, elastase, cathepsin G, and proteinase 3, were absent. Accordingly, neutrophils from this patient were incapable of producing neutrophil extracellular traps (NETs) in response to ROS and were unable to process endogenous cathelicidin hCAP-18 into the antibacterial peptide LL-37 in response to ionomycin. In immature myeloid cells from patient bone marrow, biosynthesis of CTSC and neutrophil serine proteases appeared normal along with initial processing and sorting to cellular storage. In contrast, these proteins were completely absent in mature neutrophils, indicating that CTSC mutation promotes protease degradation in more mature hematopoietic subsets, but does not affect protease production in progenitor cells. Together, these data indicate CTSC protects serine proteases from degradation in mature immune cells and suggest that neutrophil serine proteases are dispensable for human immunoprotection.